Osmosis urbana (2017)
Over the next few years, approximately 30 km of an urban profile will be built to completely change the way we live in the city. We could imagine that this great infrastructure, perhaps, will be a wall that will divide the city in two, a system so high that it will block the visuals from one side to another, a limit that will cover several green spaces, giving rise to the darkness. For some the construction that is going to develop is seen as the chaos that is going to take the city, nevertheless it can be seen like an opportunity to create a different architecture that contemplates the dynamics of the city. This imaginary is the starting point for the development of this project; Where it is proposed to propose from the architecture like infrastructure, and like this one has the capacity to transform the city. The idea was developed...